Applications of Chaos Sequence in Intelligent Transportation System - Yao Zhang; Licai Yang; Haiqing Liu; Lei Wu (Institute of Advanced Engineering and Science, 2013)
Vehicular Ad-Hoc Network (VANET) is an essential technology to improve safety and efficiency of Intelligent Transportation System (ITS), it provides vehicle to vehicle as well as vehicle to roadside unit (RSU) wireless communications, so that on board unit (OBU) located in vehicles can share messages related to road traffic with not only other OBU in the same VANET but also transportation management centre depending on retransmission of RSU. It is very important to detect and transmit real time messages of road traffic condition in VANET. This paper presents two application schemes for VANET based on chaos sequence: traffic flow forecast and vehicle secret communications. The principles of these schemes are introduced separately, and performances are verified by theoretical analysis and simulation. DOI: http://dx.doi.org/10.11591/telkomnika.v11i9.3270